Emerging Targeted Therapies for Castration-Resistant Prostate Cancer - Adamo, Vincenzo; Noto, Laura; Franchina, Tindara; Chiofalo, Giuseppe; Picciotto, Maria; Toscano, Giuseppe; Caristi, Nicola (Frontiers in Endocrinology, 2012)
Until recently, few therapeutic options were available for patients with castration-resistant prostate cancer (CRPC). Since 2010, four new molecules with a demonstrated benefit (sipuleucel-T, cabazitaxel, abiraterone and denosumab) have been approved in this setting, and to-date several other agents are under investigation in clinical trials. The purpose of this review is to present an update of targeted therapies for CRPC. Presented data are obtained from literature and congress reports updated until December 2011. Targeted therapies in advanced phases of clinical development include novel hormone-therapeutic, intracellular molecular pathways inhibiting, anti-angiogenic, bone microenvironment targeting and immunotherapeutic agents. Radium-223 and MDV3100 demonstrated a survival advantage in phase III trials and the road for their introduction in clinical practice is rapidly ongoing. Results are also awaited for phase III studies currently underway or planned with new drugs given as monotherapy (TAK-700, cabozantinib, tasquinimod, PROSTVAC-VF, ipilimumab) or in combination with docetaxel (custirsen, aflibercept, dasatinib, zibotentan). Optimal timing, right combination and/or sequencing of emerging therapies as well as use of more sensitive biological markers to individualize therapies for CRPC remain challenging and studies to investigate these aspects are needed.